Analysis of Parenting Patterns to Improve Children's Psychosocial Development: Systematic Review - Tisnawati; Delima; Herwati (proceedinginternational, 2024)
Parenting styles play a very important role in children's psychosocial development. Psychosocial development is personality development related to behavioral and social relationships. Psychosocial development has stages, and each stage has a critical period or a developmental task that must be passed. This is where the role of the family is needed as the first educator, in creating good psychosocial development. This research aims to develop parenting patterns to improve children's psychosocial development. The systematic review method is used to search for articles in electronic databases, namely Google Scholar, Research Gate, and PubMed/Medline. The search strategy method uses PRISMA (Preferred Reporting Items for Systematic Review and meta-analysis) through four stages consisting of identification, screening, eligibility, and finally inclusion. The search was limited to publication year (2015 to 2023), article type "research article", and Open Access. Articles must be complete manuscripts, published in nationally or internationally accredited journals. Analysis carried out by the author of 6 relevant articles found that positive and supportive parenting styles, which include providing love, attention, appropriate discipline, and open communication between parents and children, contribute significantly to improving children's psychosocial development. In addition, an approach that is oriented towards understanding individual children, understanding their needs, and providing space for self-expression, also plays an important role in establishing balanced psychosocial development. By understanding the importance of positive parenting, parents can play an active role in helping their children grow into psychosocially healthy individuals, who have good social skills, and the ability to overcome the stress and challenges of daily life. This research contributes to further understanding of the important role parents play in shaping their children's psychosocial future.